Structural Defects Control the Energy Level Alignment at Organic/Organic Interfaces. Issue 5 (1st April 2014) - Yonezawa, Keiichirou; Hinderhofer, Alexander; Hosokai, Takuya; Kato, Kengo; Makino, Rintaro; Schreiber, Frank; Ueno, Nobuo; Kera, Satoshi
<x xml:space="preserve">Abstract</x> The dependence of the energy level alignment (ELA) on structural defects at an organic/organic heterojunction (OOH) of perfluoropentacene (PFP)‐on‐diindenoperylene (DIP) was investigated using X‐ray scattering and ultraviolet photoelectron spectroscopy. The density of structural defects near the interface between the PFP and DIP layers was varied by changing the growth temperature of the DIP film. A direct relationship was found between the defect density and the ELA at the OOH; the ELA together with the change in the electrostatic potential (quasi‐interface dipole layer) at the OOH varies systematically with the defect density near the interface. This indicates that a key factor affecting the ELA is the electrostatic potential change across the OOH interface, which is produced by electron transfer from DIP occupied gap states to PFP unoccupied gap states. These gap states originate from the defects and are effectively controlled by adjusting the growth conditions of the organic films. As a result, the ELA at OOH interfaces can be controlled by the density of structural defect, which is important for organic devices employing OOHs, such as organic photovoltaic cells.